ASESMEN KEBUTUHAN BINA GERAK DAN MOBILITAS PESERTA DIDIK DI SEKOLAH INKLUSI DAN SLB - Nilna Uffi Al'Azmi; Watini; Siti Suarti; Sujarwanto; Endang Pudjiastuti Sartinah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify, analyse, and design movement and mobility intervention programmes for students with mobility impairments in inclusive schools and special needs schools (SLB). Through a comprehensive multi-source approach, this study explores a systematic assessment framework that includes the identification of mobility impairments, assessment of gross and fine motor skills, and evaluation of mobility issues including orientation, independence, and coordination. Data were collected from three main sources: assessment instruments from Sultan Ageng Tirtayasa University, the Inclusive Education Implementation Guidelines from the Ministry of Education and Culture, and practical guidelines from SLB-A Pembina Jakarta. The results of the study indicate that motor skills assessment must be conducted in a multi-dimensional manner involving a multidisciplinary team of professionals. The main findings identified 11 movement competencies with 37 specific assessment indicators, a percentage-based quantitative assessment system, and a qualitative approach based on independence. This article also presents recommendations for structured and personalised intervention programmes based on the assessment results, including structured motor exercises, school environment modifications, and inter-professional collaboration. The implementation of this comprehensive assessment is expected to improve the quality of inclusive education services and the independence of students with mobility impairments.